Antibiotic use at planned central line removal in reducing neonatal post-catheter removal sepsis: a systematic review and meta-analysis - Ji, Ruoyu; He, Zhangyuting; Zhou, Jiawei; Fang, Shiyuan; Ge, Lili (Frontiers in Pediatrics, 2024)
Background: Post-catheter removal sepsis (PCRS) is a notable complication of indwelling central venous catheters (CVCs) in neonates, which is postulated to be secondary to the disruption of biofilms formed along catheter tips up on CVCs removal. It remains controversial whether this could be prevented by antibiotic use upon CVCs removal. We aimed to evaluate the protective effect of antibiotic administration at the time of CVCs removal. Methods: We searched through PubMed, EMBASE, Cochrane databases and reference lists of review articles for studies comparing the use of antibiotics versus no use within 12 hours of CVCs removal. Risk of bias was assessed using the modified Newcastle-Ottawa Scale and Cochrane risk-of-bias tool accordingly. Results of quantitative analyses were presented as mean differences (MD) or odds ratio (OR). Subgroup and univariate meta-regression analyses were performed to identify heterogeneity. Results: The review included 470 CVCs in the antibiotic group and 658 in the control group. Antibiotic use within 12 hours of CVCs removal did not significantly reduce the incidence of PCRS (OR=0.35, 95% CI: 0.08 to 1.53), but was associated with a lower incidence of post-catheter removal blood stream infection (OR=0.31, 95% CI: 0.11 to 0.86). Dosage of vancomycin and world region were major sources of heterogeneity. Conclusion: Antibiotic administration upon CVCs removal does not significantly reduce the incidence of PCRS but offers less post-catheter removal blood stream infection. Whether this will be converted to better clinical outcomes lacks evidential support. Further randomized controlled studies with longer follow-up are needed.